Pengaruh Edukasi Bullying Terhadap Tingkat Pengetahuan pada Siswa atau Siswi SMP Methodist Romalbest Medan - Zebua, Agus Nurvianus; Silaen, Harsudianto (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Bullying is also known as bullying. In Indonesian bullyng is a process, technique, or approach to hurt or intimidate others directly or indirectly. Bullying is a serious problem that occurs at various levels of education, including junior high school. Of the total number, 98 students or around 30% mentioned that they had reported being a victim of bullying at school. The fact that there are still many students who say below their low level of knowledge about the effects and dangers of bullying.  To determine the effect of bullying education on the level of knowledge of students at Romalbest Methodist Junior High School in Medan. Quantitative method with Cross Sectional research design and using one group pretest - posttest design method. The sampling technique in this researcher was purposive sampling with a total trial sample of 30 students with varied demographic characteristics, consisting of 12 men (40.0%) and 18 women (60.0%). The results showed that before education, 83.3% of students had low knowledge. After education, 93.3% of students have good knowledge. Wilcoxon test showed a p value = 0.000 (p < 0.05), which means there is a significant increase after education. Bullying education is effective in improving students' knowledge. It is hoped that this program can be applied more widely to prevent bullying in schools. Students are expected to be more active in understanding and implementing bullying education to create a safe and comfortable school environment.